Fisheries cooperation in the South China Sea : evaluating the options - Zhang, Hongzhou (2019)
Given the complicated nature of the South China Sea (SCS) disputes, resolving the disputes in the foreseeable future remains highly unlikely. Proper management of these disputes to ensure stability in the South China Sea becomes a priority. There is a general consensus that the best approach for managing the disputes in the SCS is to set aside the sovereignty disputes and jointly develop and manage the natural resources, such as fisheries. While advancing fisheries cooperation in the SCS has been increasingly recognized as a political, ecological, socioeconomic and security imperative, two crucial questions remain insufficiently addressed: what objectives should be achieved via fisheries cooperation in the SCS and are the prevailing fisheries cooperation options feasible and effective in achieving these objectives? The author makes the case that three primary objectives need to be accomplished, namely, 1) achieving food security and economic development, 2) ensuring sustainable fishery and protecting marine environment, and 3) preventing fishing conflicts and disputes. Using these three objectives as evaluation criteria, the author then investigates the feasibility and effectiveness of three prevailing options, including Marine Protected Areas (MPA)/Marine Peace Park, Regional Fishery Management Organizations (RFMO), and aquaculture.